PERJUANGAN MENUJU FAIR TRADE: PENGALAMAN APIKRI DALAM MEMEDIATORI PENGRAJIN LOKAL DAN D’ BEST FURNITURE DALAM MENSIASATI ECO-LABELING - Sugiarto Pramono (Universitas Wahid Hasyim Semarang, 2012)
Abstract This paper describes the experience of two types of fair trade actors, APIKRI and D'Best Furniture (first: non governmen organization and second: companies) in the fight for fair trade values​​. Commitment to the values ​​of justice in the midst of market anarchism is a tough job. Orientation profit alone often makes the market justifies a variety of ways. Both organizations use creativity to still be able to survive in the anarchic market dynamics. Key Word: Fair Trade, fairness, Free Trade